Detoxification activity and energy cost is attenuated in whiteflies feeding on Tomato yellow leaf curl China virus‐infected tobacco plants. Issue 5 (28th July 2013) - Luan, J.‐B.; Wang, Y.‐L.; Wang, J.; Wang, X.‐W.; Liu, S.‐S.
Abstract: The begomovirus Tomato yellow leaf curl China virus (TYLCCNV) can benefit its vector, the whitefly Bemisia tabaci, through suppressing the defences of their shared host plants. However, the mechanisms of this vector−virus mutualism remain largely unknown on the insect side of the interaction. Here, we compared the transcriptional profiles of female adult whiteflies of B. tabaci Middle East‐Asia Minor 1 feeding on TYLCCNV‐free and TYLCCNV‐infected tobacco plants using the next‐generation sequencing technique and quantitative real‐time PCR. Interestingly, the genes involved in the oxidative phosphorylation (OXPHOS) pathway and detoxification enzyme were down‐regulated in whiteflies feeding on virus‐infected plants. Decreased detoxification activity costs less energy, which may reduce OXPHOS activity. Moreover, the genes involved in redox activity were also down‐regulated, which may indicate that the reduced OXPHOS activity decreased reactive oxygen species production. Reduced detoxification activity is likely to attenuate energy costs, thereby enhancing the performance of whiteflies on virus‐infected plants. These results provide further insight into the mechanisms of the plant‐mediated whitefly−virus mutualism. Moreover, our study suggests that investigating the transcriptional profiles on the insect side of the interaction can advance our understanding of the tripartite interactions.